Associations of effort-reward imbalance at work and quality of life among workers after stroke: a one-year longitudinal study in Thailand - Siripan Naknoi; Jian Li; Pongrama ramasoota; Xinyue Liu; Liwei Chen; Suparat Phuanukoonnon; Ngamphol Soonthornworasiri; Orawan Kaewboonchoo (BMC Public Health, 2023)
Abstract Stroke incidence is increasing among working-age population, but the role of psychosocial stress in the workplace in predicting quality of life (QoL) after stroke onset is understudied. This longitudinal study aimed to investigate the relationship between work stress, measured by the effort-reward imbalance (ERI) model, and QoL over one-year period among 103 Thai workers who had experienced a stroke. The study evaluated the effort (E)-reward (R) ratio and over-commitment, the extrinsic and intrinsic components of the ERI model, before discharge; QoL was repeatedly measured at baseline, six months, and 12 months after discharge, respectively, using the Short Form Version 2 (SF-12v2) indicators of physical and mental health composite scores. Generalized estimating equations were used to examine longitudinal relationships between work stress at baseline and QoL over one year by testing the hypotheses that E-R ratio and over-commitment would have direct effects on QoL, and potential moderating effects of over-commitment on E-R ratio and QoL. The results supported the ERI model partially, as over-commitment was significantly associated with poor mental health (coefficient − 8.50; 95% CI: -13.79, -3.20) after adjusting baseline sociodemographic, behavioral, and clinical characteristics, while the E-R ratio was not significantly associated with physical or mental health; the interaction between the E-R ratio and over-commitment was also not significant. These findings suggest that more attention should be paid to workers’ personal coping skills and ability to handle work-related problems and prioritize interventions that address over-commitment to promote long-term mental health among workers with stroke.